The Quality of Higher Education in Public Administration in Thailand: the Side-Effects of Administrative Reform - AMPORN TAMRONGLAK (Jurnal Studi Pemerintahan, 2016)
Since the current quality framework, called Thailand Qualification Frameworks for Higher Education (TQF-HEd), has been enforced in the past years by the Office of the Higher Education Commission (OHEC), the quality of the graduates produced and the quality of teaching Public Administration particularly graduate study seems to be in the opposite directions. This paper investigates the quality of higher education in Public Administration at Master level in Thailand. Data such as curriculums, program philosophy, etc. were collected from universities offering graduate study in Public Administration. In-depth interviews were conducted from public and private universities. In the midst of the Administrative Reform in Thailand during the economic crisis in 1997, the author analyzed the impacts of the reform, particularly the influential practice of New Public Management (NPM), on the quality of teaching graduate study in Public Administration in Thailand.Key Words: Public Administration, Higher Education in Thailand, Quality of teaching, New Public Management